Detection of Usutu virus in a house martin bug Oeciacus hirundinis (Hemiptera: Cimicidae): implications for virus overwintering in a temperate zone - Šikutová, Silvie; Mendel, Jan; Mravcová, Kristína; Kejíková, Romana; Hubálek, Zdeněk; Kampen, Helge; Rudolf, Ivo (Parasitology research, 2024)
The family Cimicidae comprises ectoparasites feeding exclusively on the blood of endothermic animals. Cimicid swallow bugs specifically target swallow birds (Hirundinidae) and their nestlings in infested nests. Bugs of the genus Oeciacus are commonly found in mud nests of swallows and martins, while they rarely visit the homes of humans. Although-unlike other cimicid species-the house martin bug Oeciacus hirundinis has never been reported as a vector of zoonotic pathogens, its possible role in arbovirus circulation in continental Europe is unclear. Samples of O. hirundinis were therefore collected from abandoned house martin (Delichon urbicum) nests in southern Moravia (Czech Republic) during the 2021/2022 winter season and checked for alpha-, flavi- and bunyaviruses by RT-PCR. Of a total of 96 pools consisting of three adult bugs each, one pool tested positive for Usutu virus (USUV)-RNA. Phylogenetic analysis showed that the virus strain was closely related to Italian and some Central European strains and corresponded to USUV lineage 5. The detection of USUV in O. hirundinis during wintertime in the absence of swallows raises the question for a possible role of this avian ectoparasite in virus overwintering in Europe.
Keywords: Seasons; Overwintering; Česká republika; Usutu virus; Bird Diseases; RNA, Viral; Czech Republic; Cimicidae; nemoci ptáků; zvířata; fylogeneze; Hirundo rustica; House martin; Flavivirus; Oeciacus hirundinis; Phylogeny; roční období; RNA virová; Animals